2010
DOI: 10.1111/j.1467-3010.2010.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of breakfast cereals in the UK diet: headline results from the National Diet and Nutrition Survey (NDNS) year 1

Abstract: The first results from the new rolling programme of the UK's National Diet and Nutrition Survey (NDNS) have been published. The survey found that breakfast cereals were consumed by about 50% of those children and adults taking part, and the average amount eaten was generally in line with the recommendations by the European breakfast cereal association on portion size. Breakfast cereals provided only a small proportion of the total intake of fat, saturated fat, non-milk extrinsic sugars and sodium, as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The latest national survey from the United Kingdom found that whereas breakfast cereals contribute 3–5% of the daily energy intake and 2–5% of dietary fiber intake, they provide only 1% of fat and 1–2% of sodium in the total diet ( 3 ). Similarly, breakfast cereals contribute only 2.1–2.6% of total sodium intake in adults in the United States ( 71 ) and <2.5% in Australia ( 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest national survey from the United Kingdom found that whereas breakfast cereals contribute 3–5% of the daily energy intake and 2–5% of dietary fiber intake, they provide only 1% of fat and 1–2% of sodium in the total diet ( 3 ). Similarly, breakfast cereals contribute only 2.1–2.6% of total sodium intake in adults in the United States ( 71 ) and <2.5% in Australia ( 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of breakfast cereals in a balanced diet has been recognized for many years ( 1 – 3 ). Dietary guidelines note that the high nutrient density of breakfast cereals (especially those that are whole grain or high in cereal fiber) makes them an important source of key nutrients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion in the breakfast of cereal-based products has been demonstrated to be a valid choice for increasing the nutritional quality of one’s diet [22,23]. Despite their health effects, breakfast cereals are a heterogeneous category of food products and different international surveys report a great variability in their nutritional composition, mostly for sugar and salt content [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nutrient and non‐nutrient compounds in whole grains (e.g. lignans, tocotrienols, phenolic compounds) are associated with improved health status (see Table and Table ) . During the refining process, the bran is partially and/or completely removed.…”
Section: Resultsmentioning
confidence: 99%